“Being-Placed before God”: Reading the Early Heidegger’s Phenomenology of Liturgy with Jean-Yves Lacoste - Jorge Luis Roggero (Religions, 2021)
This article aims to demonstrate, by means of a comparison with Lacoste’s proposal, that we can find a particular phenomenology of liturgy in the early Heidegger’s phenomenology of religion, centered in the structure of “being-placed before God”. His examination of this structure manages to go deeper than Lacoste in order to account for the essence of human existence. With this purpose in mind, in the first section of the article I will the present the basic features of the liturgical experience, as it is introduced in Experience and the Absolute. In the second section, I will analyze the early Heidegger’s phenomenology of religion and its interpretation of Christian factical life experience. Finally, in the third section, I will bring the insights from both sections together to establish the particularities of Heidegger’s phenomenology of liturgy.